Cyber Sovereignty and International Law: Legal Challenges in the Digital Age - Maulana Anwar; Afkarul Azmi (Iustitia: Journal of Legal Theory, Politics, and International Relations, 2026)
This article examines the evolving doctrine of cyber sovereignty within contemporary international law through a non-empirical doctrinal and comparative legal approach. It reconstructs the normative foundations of sovereignty in cyberspace by analyzing the United Nations Charter, customary international law, state responsibility principles, and national regulatory frameworks, including Indonesia’s Electronic Information and Transactions Law and related implementing regulations. The study clarifies the relationship between jurisdiction, due diligence, and attribution in determining the legality of state conduct in cross-border cyber operations. Comparative legal policy analysis demonstrates that divergent regulatory models ranging from sovereignty-centric territorial control to cooperative multistakeholder governance reflect competing interpretations of sovereignty rather than its decline. The findings indicate that cyber sovereignty functions as a relational and adaptive principle conditioned by proportionality, human rights safeguards, and cooperative responsibility. By integrating doctrinal interpretation with comparative assessment of state practice, the article advances a structured analytical framework that reconciles sovereign autonomy with global digital interdependence and contributes to the development of coherent international legal standards for cyberspace governance.